Shrek [videorecording (Blu-Ray)] - Steig, William, 1907-2003 (Universal Pictures Home Entertainment, 2021)
Relive every moment of Shrek's daring quest to rescue feisty Princess Fiona, with the help of his lovable loudmouthed Donkey, and win back the deed to his beloved swamp from scheming Lord Farquaad.